Atypical Neurological Manifestations of COVID-19 - Gupta, Ishita (Cureus, 2020)
The novel coronavirus (SARS-CoV-2), belonging to a group of RNA-enveloped viruses and believed to be transmitted by aerosol route, is a worldwide pandemic. Many studies have described typical clinical manifestations such as fever, cough, fatigue, diarrhea, and nasal congestion. However, to our knowledge, there are minimal studies on the neurological manifestations in SARS-CoV-2 positive patients. Our review aims to identify the various neurological manifestations in SARS-CoV-2 positive patients, which could be an added advantage in the early diagnosis and prevention of further complications of the nervous system.